Sleep-Wake Behavior in Elite Athletes: A Mixed-Method Approach - de Blasiis, Kévin; Joncheray, Hélène; Elefteriou, Julia; Lesenne, Chloé; Nedelec, Mathieu (Frontiers in Psychology, 2021)
Purpose: Using a mixed-method approach, this investigation aimed to examine athletes’ sleeping patterns along with the socio-physiological acute and chronic stressors affecting their sleep. Methods: Fifteen elite athletes (Mage= 21.7 years; SD = 2.2) were monitored daily during a typical in-season training period (20 ± 1 days) and completed individual semi-structured interviews. Their sleep was analysed using actigraphy and sleep diaries. A content analysis method was used to assess qualitative interviews. Results: Three factors influencing sleep emerged from the qualitative interview analyses, i.e. sleep environment, training and study requirements. Half the athletes (8/15) complained about their sleeping environment with noise and/or bedroom temperature and/or mattress quality and/or light exposure presented as an issue. ‘Complainers’ notably exhibited impaired (p<0.05) sleep efficiency and wake after sleep onset compared with ‘non complainers’. Daily training load showed correlations (p<0.05) with wake after sleep onset and sleep onset latency. ‘Student athletes’ exhibited later bedtime and earlier wake-up time compared with ‘non-student athletes’, leading to a reduced total sleep time (6:50 ± 1:13 vs. 7:06 ± 0:53; p<0.05; d=0.20). Conclusion: An individualised assessment of sleep using actigraphy and interviews, with consideration to various socio-physiological factors, is recommended. Individualised sleep interventions with consideration to physiological (e.g. training load), behavioural (e.g. screen use) and environmental factors (e.g. room temperature, noise, mattress), can then be provided to each athlete.